Profiling of widely targeted metabolomics for the identification of chemical composition in epidermis, xylem and pith of Gleditsiae Spina. (11th March 2022) - Ya, Huiyuan; Li, Huiru; Liu, Xianghui; Chen, Ye; Zhang, Jingxiao; Xie, Yanfu; Wang, Mengshu; Xie, Wanyue; Li, Shipeng
Abstract: Gleditsiae Spina, the thorn of Gleditsia sinensis Lam., has a long history of being used as a traditional medicine in East Asian countries. However, only a few biologically active substances have been identified from it. In this study, the epidermis, xylem and pith of Gleditsiae Spina, respectively Gs‐E, Gs‐X and Gs‐P, were studied. We used a widely targeted metabolomics method to investigate the chemical composition of Gs‐E, Gs‐X and Gs‐P. A total of 728 putative metabolites were identified from Gleditsiae Spina, including 211 primary metabolites and 517 secondary metabolites. These primary and secondary metabolites could be categorized into more than 10 different classes. Flavonoids, phenolic acids, lipids, amino acids and derivatives, and organic acids constituted the main metabolite groups. Multivariate statistical analysis showed that the Gs‐E, Gs‐X and Gs‐P samples could be clearly separated. Differential accumulated metabolite (DAM) analysis revealed that more than half of the DAMs exhibited the highest relative concentrations in Gs‐E, and most of the DAMs showed the lowest relative concentrations in Gs‐X. Moreover, 11 common differential primary metabolites and 79 common differential secondary metabolites were detected in all comparison groups. These results further our understanding of chemical composition and metabolite accumulation of Gleditsiae Spina.